Correlations between microstructure and crystallization of the fluorinated terpolymer of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride. Issue 20 (16th October 2019) - Ok, Salim; Hartmann, Brigitte; Duran, Hatice; Eickmeier, Henning; Haase, Markus; Scheler, Ulrich; Steinhart, Martin
ABSTRACT: Random THV terpolymers consisting of tetrafluoroethylene (TFE), hexafluoropropylene (HFP), and vinylidene fluoride (VDF) are viable alternatives to polytetrafluoroethylene (PTFE) combining excellent chemical stability and thermoplastic processability. Although the properties of THV may be modified by crystallization, little is known on how crystallization is influenced by the chain microstructure of THV. We analyzed the chain microstructure of THV‐221G by solid‐state 19 F NMR spectroscopy under fast magic angle spinning, revealing that THV‐221G contains 43.8 mol % TFE, 46.0 mol % VDF, and 10.2 mol % HFP. Sequence analysis revealed that the TFE units are preferentially located next to other TFE units. The HFP units, which are obstacles to crystallization because of their bulky CF3 side groups, are preferentially located next to VDF units. WAXS measurements correspondingly revealed the presence of THV‐221G crystals with PTFE‐like packing and of further THV‐221G crystal populations with widened d ‐spacings caused by the incorporation of certain amounts of HFP units into the THV‐221G crystals. Under confinement imposed by the cylindrical nanopores of self‐ordered alumina, the THV‐221G melting point decreased with decreasing pore diameter. Although direct impingement of the growing THV‐221G crystals on the pore walls is unlikely, the geometric confinement limits the access of growing THV‐221G crystals to crystallizable THV‐221G chain segments. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 1402–1408 Abstract : THV terpolymers consist of tetrafluoroethylene (TFE), hexafluoropropylene, and vinylidene fluoride units. NMR microstructure analysis of the exemplary THV grade THV‐211G revealed the presence of significant amounts of TFE–TFE diads and TFE–TFE–TFE triads, whereas WAXS indicated the presence of PTFE‐like crystals. Melting point depression in the hard confinement of cylindrical nanopores was attributed to limited access of growing crystals to crystallizable THV chain segments.